Mendesain Intervensi Kesehatan dengan Memanfaatkan WhatsApp untuk Mencegah Stunting pada Balita Selama Masa Pandemi COVID-19 - Rizky Puspitarini; Nuzulul Kusuma Putri; Lies Permana (Jurnal Kesehatan Komunitas, 2022)
Stunting case in Indonesia is still high, so the provision of complete health information for toddler health is extremely needed during the COVID-19 pandemic. Therefore, this study aims to design a health information service online by using WhatsApp to prevent toddler stunting in the rural community. This study was action research in which a co-design methodology was used to design the health information service. This study involved the health front, midwifery, nutritionist, and village apparatus in which they were interviewed and followed focus group discussion (FGD). In addition, the USE questionnaire was used to measure the effectiveness of the health information service that had been designed. The results of the interview and FGD showed that rural people knew more about the use of WhatsApp than other online communication platforms. In addition, during the COVID-19 pandemic, there were a number of health programs that would be stopped. As a consequence, online interactive health information service was extremely needed to promote the sustainability of health programs in the rural community. Furthermore, the results of the USE questionnaire showed the average percentage of usefulness, ease of use, ease of learning, and satisfaction of the online health information service was 85,43%. This indicates that the hotline stunting program (INSTING), an online health information service, is extremely eligible to be applied in the rural community in conducting communication regarding health information during the COVID-19 pandemic.